2006
DOI: 10.1002/jcc.20548
|View full text |Cite
|
Sign up to set email alerts
|

σ and π contributions to the induced magnetic field: Indicators for the mobility of electrons in molecules

Abstract: Abstract:The authors discuss the role of the and contributions to the induced magnetic field for simple hydrocarbons containing a double or a triple bond, as well as for benzene and cyclobutadiene. While the magnetic field induced by the electrons is short-ranged, the system is responsible for the formation of long-range cones. These cones influence the chemical shift of atoms by additional shielding (for aromatic) or deshielding (for antiaromatic molecules) contributions. While the hydrogen atoms of benzene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 46 publications
4
130
0
Order By: Relevance
“…In addition, they applied the gauge-including magnetically induced current (GIMIC) method to [c- Al 4 ] 2-and [c-Al 4 ] 4-clusters to elucidate the type of aromaticity in these aromatics [37][38][39]. Heine et al [40,41] represented graphically with three-dimensional isosurfaces the induced magnetic field of cyclic molecules and showed that the appearance of the magnetic response characterizes aromatic, antiaromatic and non-aromatic molecules. They also showed that the z-component of the induced magnetic field is directly connected to NICS zz .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they applied the gauge-including magnetically induced current (GIMIC) method to [c- Al 4 ] 2-and [c-Al 4 ] 4-clusters to elucidate the type of aromaticity in these aromatics [37][38][39]. Heine et al [40,41] represented graphically with three-dimensional isosurfaces the induced magnetic field of cyclic molecules and showed that the appearance of the magnetic response characterizes aromatic, antiaromatic and non-aromatic molecules. They also showed that the z-component of the induced magnetic field is directly connected to NICS zz .…”
Section: Introductionmentioning
confidence: 99%
“…22,34 Other more sophisticated approaches are those based on molecular dissected NICS 31,32 conjointly with their bi-or tri-dimensional plots. 34,[37][38][39][40][41] It is also important to highlight that the quantitative relationship between shielding and ring current strengths has been rigorously analyzed in the past. [42][43][44][45] In these works, it is assumed that the wire carrying the ring current is circular and innitely thin; thus, the induced magnetic eld is easily determined from classical electrodynamics, using the Biot-Savart's law.…”
Section: 33-35mentioning
confidence: 99%
“…The different NICS zz values perfectly reproduce the trend obtained from HOMA and FLU. Finally, it may be pointed out that the present aromaticity analysis could be positively complemented in the future by the dissection of the NICS in r and p contributions [88,89]. The geometries of benzene and hexaprismane were also optimized and characterized at the MP2 level, constraining the D 6h symmetry (see Table 2 for details).…”
Section: Resultsmentioning
confidence: 99%